Efektivitas Kompres Dingin dalam Menurunkan Intensitas Nyeri pada Pasien Fraktur: Scoping Review (Inovasi Kesehatan Global, 2026)
Cold compresses or cryotherapy are one of the non-pharmacological therapies often used in nursing practice to help reduce pain, especially in patients with fractures. Fractures are often accompanied by acute pain that can inhibit mobilization, prolong recovery time, and reduce patient comfort. Therefore, a safe, effective, and easy-to-use pain management method is needed. This article was compiled with the aim of identifying and mapping scientific evidence regarding the effectiveness of cold compresses in reducing pain intensity in fracture patients. This study used the Arksey and O'Malley model in conducting the analysis, with articles searched through PubMed, ScienceDirect, and Google Scholar for the 2021–2025 publication period. The article selection process followed the PRISMA flow. A review of ten articles showed that most studies used quantitative designs, both experimental and quasi-experimental. The results of the analysis of 11 articles consisted of 8 quantitative articles with experimental and quasi-experimental designs, while 2 articles were case studies. These articles generally discuss the effectiveness of cold compresses in reducing pain intensity in fracture patients using various measurement instruments, such as NRS, VAS, Wong-Baker Faces Scale, and Bourbanis Pain Scale. In addition to reducing pain, several studies also reported that cold compresses can reduce edema, increase mobility, and improve patient comfort. However, variations in the duration, frequency, and method of cold compress application were still found, so there is a need to develop a more standardized protocol in nursing practice.